A Comparative Study of Pension Systems Italy and Turkey - TÜRKMEN, ESAT NURİ (İstanbul Kültür Üniversitesi, 2024)
This study aims to compare the pension systems of Italy and Turkey, providing an in-depth analysis for both countries. Pension systems are designed to help individuals with financial planning throughout their lives, offer protection against personal uncertainties, and distribute economic risks across generations. Beyond financial security, these systems provide dignity and stability as people age. The study examines the historical development, structure, financial sustainability, eligibility criteria, demographic characteristics, reforms, and future expectations of the pension systems in Turkey and Italy, highlighting similarities and differences. Ultimately, it aims to contribute to the literature by presenting a comparative analysis of the pension systems of these two countries.
İtalya ve Türkiye Arasındaki Emeklilik Sistemlerinin Karşılaştırılması
Yüksek lisans tezi.
Keywords: Pension System; Turkey; Italy; Economic Reforms; Financial Sustainability